2010
DOI: 10.1080/13546783.2010.526786
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural study of hindsight bias and conditional probabilistic reasoning

Abstract: In this fMRI study, we investigated Theory of Mind (ToM) in patients with paranoid schizophrenia. We hypothesized that the network supporting the representation of intentions is dysfunctional in patients with schizophrenia dependent on the type of intention involved. We used a paradigm including a control condition (physical causation) and three intention conditions (private intention, prospective social intention and communicative intentions) differing in the degree of social interaction. Patients showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In Easterners' dialectical thinking, the tendency to consider two contradictory possibilities was observed in a cross-cultural study on hindsight bias. Yama, Manktelow, Mercier, Van der Henst, Do, Kawasaki, and Adachi (2010) confirmed that hindsight bias was stronger among Easterners than Westerners (e.g., Choi & Nisbett, 2000) in a study with Japanese, Korean, British, and French participants. The Easterners were more inclined to think dialectically when they met a plausible outcome from a vignette and an unexpected outcome, while Westerners' judgment was less affected by the unexpected outcome.…”
Section: This Distinction Has Been Discussed In Terms Of the Contrastsupporting
confidence: 63%
“…In Easterners' dialectical thinking, the tendency to consider two contradictory possibilities was observed in a cross-cultural study on hindsight bias. Yama, Manktelow, Mercier, Van der Henst, Do, Kawasaki, and Adachi (2010) confirmed that hindsight bias was stronger among Easterners than Westerners (e.g., Choi & Nisbett, 2000) in a study with Japanese, Korean, British, and French participants. The Easterners were more inclined to think dialectically when they met a plausible outcome from a vignette and an unexpected outcome, while Westerners' judgment was less affected by the unexpected outcome.…”
Section: This Distinction Has Been Discussed In Terms Of the Contrastsupporting
confidence: 63%
“…Nevertheless, this was contrary to what we had expected. On the basis of the hypothesis from Choi and Nisbett (; see also Yama et al, ) that a holistic thinking style fosters hindsight bias, we had proposed that the same might hold for the effect of further reading biased materials. A more holistic thinking style was generally associated with greater perceptions of likelihood, inevitability, and foreseeability; however, it did not lead to pronounced effects of article version on readers' perceptions.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies (e.g. Choi & Nisbett, ; Yama et al, ) have often used nationality as a proxy for analytic versus holistic thinking style. Our research suggests, however, that holistic thinking does not necessarily go along with East Asian nationality, especially when answering questionnaires in English.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we should point out the cultural differences in hindsight bias between Westerners and Easterners when considering such trial cases, because it has been shown that this bias is greater among Easterners than Westerners (Choi & Nisbett, 2000; Yama et al, 2010). Choi and Nisbett (2000) explain this cultural difference as that Easterners have more complex causal models for events than the Westerners do.…”
Section: Hindsight Bias and Legal Decision Makingmentioning
confidence: 99%